Comparison of the effect of vaginal misoprostol alone and in combination with evening primrose capsules on the course of labor in pregnant women candidates for termination of pregnancy - Mobaraki, Noushin; Tabrizian, Shervin; Isazadehfar, Khatereh; Ghorbani, Shahrzad (International Journal Of Community Medicine And Public Health, 2023)
Background: Induction of labor at any time before the spontaneous onset of labor is indicated when the benefits of termination of pregnancy for the mother and fetus outweigh the benefits of continued pregnancy. The aim of this study was to compare the effect of vaginal misoprostol alone and in combination with evening primrose capsule on the course of labor in pregnant women candidates for termination of pregnancy. Methods: In this double-blind randomized clinical trial, 30 pregnant women were candidates for termination of pregnancy. At the time of referral, the examination was performed to calculate the bishop score (primary outcome) and the partograph was recorded and plotted once every hour until the end of labor. Length of active phase of labor (from dilatation 3-6 cm to birth), type of labor, Apgar score of the first and fifth minute of the baby and volume of postpartum hemorrhage and pain intensity every 30 minutes was recorded in two groups for up to 2 hours using a ruler. Results: The mean length of the latent labor phase in the misoprostol and evening primrose groups was 9.07±0.96 and in the misoprostol group was 10.13±0.83 hours and this difference was significant. There was no significant difference in bishop score between the two groups at the beginning of the study but after the intervention was significant. Conclusions: Our study showed that using evening primrose oil capsule instead of misoprostol is effective in induction of labor.